Determination of - Abreu,P; Adam,W; Adye,T; Agasi,E; Ajinenko,I; Aleksan,R; Alekseev,GD; Alemany,R; Allport,PP; Almehed,S; Amaldi,U; Amato,S; et al. (Zeitschrift Fur Physik C Particles and Fields, 1996)
Semileptonic decays B → D- +νX were selected from a sample of 3.1 million hadronic Z decays collected by the DELPHI detector at LEP. A topological search for semileptonic B decays to resonant and non-resonant D- π+ states was performed and the ratio of the branching fractions: Br(B → D- +νX)/Br(B → D- +νX) + Br(B0 → D- +ν) = 0.19 ± 0.10(stat) ± 0.06(syst) was determined. Taking into account this contribution, the differential decay width of B0 → D- +ν was measured as a function of the momentum transfer from the B to the D- in two separate analyses, using exclusive and inclusive methods of D- + reconstruction. The distributions were fitted over the full momentum transfer range to extract the product of |V cb| times the normalization of the decay form factor F(q max2): F(qmax2)|Vcb| = (35.4 ± 1.9(stat) ± 2.4(syst)) • 10-3. The value of |Vcb| was computed using theoretical calculations of F(q max2), giving: |Vcb| = (38.9 ± 2.0(stat) ± 2.6(syst) ± 1.7(theory)) • 10-3. The total branching fraction Br(B0 → D- +ν) was determined to be: Br(B0 → D- +ν)